The Effect of Entrepreneurial Orientation on Innovation Performance in The Wastra Industry of Kediri City - Pervitasari, Salma Arien; Susilowati, Christin (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to examine the effects of entrepreneurial orientation on innovation performance among Wastra industry entrepreneurs in Kediri City, with particular attention to the dimensions of innovativeness, risk-taking, autonomy, proactiveness, and competitive aggressiveness. Design/Methodology/Approach – This study employs a quantitative descriptive research design. Using a saturated sampling technique, all 32 Wastra industry entrepreneurs in Kediri City were selected as respondents. Data were analyzed using multiple linear regression in SPSS version 27 after passing the classical assumption tests, including normality, linearity, and heteroscedasticity tests. Findings – The results indicate that entrepreneurial orientation simultaneously has a positive and significant effect on innovation performance, explaining 55.7% of the variance in innovation performance. Partially, innovativeness, risk-taking behavior, proactiveness, and competitive aggressiveness significantly influence innovation performance, whereas autonomy has no significant effect. These findings suggest that strengthening entrepreneurial orientation—particularly its significant dimensions—is essential for fostering innovation and sustaining competitiveness in the Wastra industry.   Originality/Value This research is original as a replication study that tests entrepreneurial orientation dimensions within the Wastra industry context in a developing city. The findings provide practical value by identifying which orientations most significantly influence innovation performance, enabling entrepreneurs to focus on the most impactful capabilities.